Organic Pollutants - Monitoring, Risk and Treatment 2013
DOI: 10.5772/53699
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Organic Pollutants in Water

Abstract: Additional information is available at the end of the chapter http://dx.doi.org/10.5772/53699. Introduction " photocatalyst is defined as a substance which is activated by adsorbing a photon and is capable of accelerating a reaction without being consumed [ ]. These substances are invariably semiconductors. Semiconducting oxide photocatalysts have been increasingly focused in recent years due to their potential applications in solar energy conversion and environmental purification. Semiconductor heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 52 publications
0
89
0
1
Order By: Relevance
“…Thus, the aforementioned PANI-TiO 2 interactions result in the PANI-TiO 2 synergistic effect that hinders the recombination process and increases TiO 2 activity under ultraviolet (UV) and Vis irradiation [13]. Photocatalysis then proceed by the typical mechanism, known for TiO 2 : e CB − and h VB + transform H 2 O and O 2 into OH radicals, which in turn degrade the organic pollutants [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the aforementioned PANI-TiO 2 interactions result in the PANI-TiO 2 synergistic effect that hinders the recombination process and increases TiO 2 activity under ultraviolet (UV) and Vis irradiation [13]. Photocatalysis then proceed by the typical mechanism, known for TiO 2 : e CB − and h VB + transform H 2 O and O 2 into OH radicals, which in turn degrade the organic pollutants [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Many reports about the effect of pH on photocatalytic degradation of organic compounds in water resource have been written [20,[28][29]. In fact, the interpretation of the pH-dependent photodegradation of HA on TiO 2 is a very difficult task because of its multiple roles.…”
Section: Effect Of Ph Valuesmentioning
confidence: 99%
“…According to Akpan and Hameed [16] most study confirmed that the use of catalysts such as TiO2(SY) is effective for degradation at lower pHs, similar to the ones reported elsewhere, which is attributed to the strong electrostatic field of the Cs-TiO2(SY)/Glass photocatalyst enhancing photocatalytic performance between the surface of TiO2(SY) catalyst with positive charges, and the charges from solution, which is mostly negative [13,17]. However, lower pHs could adversely affect the catalyst during the photocatalytic process [16] making it necessary that the adsorption characteristics of MO on the surface of Cs-TiO2(SY)/Glass photocatalyst is investigated prior to the extended photodegradation process. According to Liu, et al [10] Cs could be used as an adsorbent at an optimal pH of between 3-6.…”
Section: Effect On Ph Of Pollutant Mediummentioning
confidence: 99%